Pheromone trap colour determines catch of nontarget insects - Clare, G.; Suckling, D.M.; Bradley, S.J.; Walker, J.T.S.; Shaw, P.W.; Daly, J.M.; McLaren, G.F.; Wearing, C.H. (New Zealand Plant Protection, 2000)
Pheromone traps were operated in five regions to determine the impact of trap colour on catch of target and nontarget insects Red or green coloured pheromone sticky traps caught fewer native and introduced bees compared to the standard white traps and yellow or blue traps Honey bees (Apis mellifera) were caught mainly in white followed by blue traps while bumble bees (Bombus spp) were most attracted to blue traps with most of the remainder caught in white traps Native bee (Lasioglossum and Hylaeus spp) catches were greatest in white traps followed by yellow traps with a few in green traps There was no significant difference in catch of the target species Cydia pomonella or Epiphyas postvittana with trap colour Replacement of the white traps with green or red traps is recommended to reduce nontarget impacts on bees